Fifty Shades of Translation: On the Patterns in the English to Polish Translation of Erotica - Karpińska, Patrycja; Olejniczak, Jędrzej (Journal of Education Culture and Society, 2019)
Aim. The aim of this article is to investigate the patterns in the translation of sex-related vocabulary from English to Polish in search for any changes regarding the markedness, poetics, and linguistic variety.Methods. The study is conducted on the pairs of English erotic novels and their Polish translations. It involves both quantitative (corpus-based methods) and qualitative (Descriptive ranslation Studies) methods.Results. The results indicate significant change in the area of marked vocabulary. In English-Polish translation, a vast majority of the marked vocabulary related to sex is replaced with unmarked vocabulary, paraphrased, or simply deleted. The qualitative analysis also suggests certain changes in the poetics of text, introduced by the means of addition. These changes mostly result in sexual encounters becoming more romanticised in translation.Conclusions. While the observed trends in translation are unmistakeable, it cannot be concluded with certainty what have led to the changes of the source text. Since the analysed texts were all published around the same time, by different publishing houses, and were translated by different translators, we are leaning towards the hypothesis of self-censorship in translation.